Al-Nudhi's additions to Al-Nasafi regarding the torment of the grave and intercession - Majid, Prof. Dr. Kamran Orahman; Al-Tayeb, L.Dr. Nawal Al-Sadiq Ahmed (Sulaimani Journal for Humanities, 2024)
The scholar Sheikh Ma'ruf al-Nawdhi was known for his numerous works and writings in Arabic and Islamic sciences. Theology and creeds received considerable attention in his poetry and compositions. This was not accidental; rather, it was one of Sheikh al-Nawdhi's aims and objectives to focus on them. As he himself says: "And indeed, the noblest of objectives is the knowledge of the foundations of religion and creeds. Whoever grasps it firmly will find happiness in both worlds. Whoever clings to its strong rope will be protected from misery and ruin. Whoever desires sound faith will be enriched by memorization and mastery. It will dispel doubts and illusions and open hearts to Islam." (Al-Fara'id, pp. 59-60) Upon examining his works, we found that his role was not limited to simply organizing books as they were, but extended to include additions and expansions on what the authors had already stated. Among the issues of theology and creed, we found the topic of the punishment of the grave to be one that has been widely discussed in our time, with some people denying it entirely and promoting this idea among the people. Al-Nawdhi, as was his custom, addressed this topic with concise and brief statements, and short verses that are like pearls and gems, brimming with profound meanings and subtle, insightful allusions. He also did so with the topic of intercession, adding to the original text, particularly in his conclusion. Therefore, we chose this topic for this brief study. The introduction to this research will present the reasons for this choice, the research objectives and problem, the researcher's methodology, and other well-known matters that must be mentioned and presented in the introductions to scholarly research.